Abordagem histórica no ensino de Química: elaboração de uma sequência de aprendizagem temática para o ensino da conservação da massa - Cortez, Cristiane Felix Martins [UNIFESP] (2021)
This thesis addresses the topic History of Science as a mainstay of the contextualized teaching of Chemistry, beginning at the re-elaboration, evaluation and validation of a Thematic Learning Sequence (SAT) in a classroom. The object of study of this sequence was the Mass Conservation Law and natural philosopher Antoine Laurent Lavoisier's contribution to Chemistry. The SAT’s evaluation was conducted from Forato’s parameters (2009), which defines the pedagogical purpose of the use of History of Science in teaching. To corroborate this, the referred sequence was implemented in particularly three classes of first year high school students of a state public school. The SAT was conducted in 8 lessons, each with a 45-minute duration. In this work, students’ responses to the first and last questionnaires, which are part of the sequence’s purpose, were analyzed, using as a basis the methodology of a content analysis of Bardin (2016). Comparing the results of the first and last questionnaires about science’s nature, a change in students’ responses was observed, exhibiting greater arguments, making use of conceptual elements explored throughout the application’s process, which lead to the conclusion that they have acquired a more critical view of science. In relation to the concept of conservation, it was noted a notorious appropriation of scientific knowledge. However, the students’ explanations were lacking, seeing that they were missing the use of a sub-microscopic model of the constitution of matter to explain the chemical transformation – which would be fundamental to the understanding of mass conservation and number of atoms.